Illocutionary Act of Dissociative Identity Disorder in the Main Character of the Split Movie - Nabilla Sekarayu Amalia (Universitas Brawijaya, 2021)
Individuals produce speech to communicate that can lead to an action, which is referred to as a speech act. This study aimed to examine one type of speech act, the illocutionary act, as portrayed by the main character in the Split movie who suffers from Dissociative Identity Disorder. The problems of this study covered: (1) the types of illocutionary acts found in the main character, (2) the perlocutionary effect related to illocutionary in the utterance produced by the main character, and (3) the reason for the main character of demonstrating the speech accommodation when he acts like an adult or kid to the addressee. The method used to conduct this study was a qualitative approach using document analysis. In analyzing the data, the researcher used the theory of the illocutionary act proposed by Searle (1976), the perlocutionary act by Austin (1962), and communication accommodation by Holmes (2013). The results showed that the main character demonstrated five types of illocutionary acts. In this movie, the perlocutionary effect was the listener’s action that the speaker wanted, or it might be unexpected. Besides, most of the accommodation used by the main character was speech convergence.